Réponses

2014-09-20T16:49:27+02:00
Bonjour

(6 x (7 - 4)) + 3 = 21

36 : ( 4+ 8) = 3

(10 - 2) x (4 + 2) = 48

(12 x (7 + 5)) - (4 x (7 + 4)) = 100
 

36:4+8=3
je me suis tromper dsl
36:(4+8)=3
merci bcp
ok
2014-09-20T16:50:58+02:00

6 x (7 - 4) + 3 = 6 x 3 + 3 = 18 + 3 = 21

36 : (4 + 8) = 36 : 12 = 3

(10 - 2) x (4 + 2) = 8 x 6 = 48

12 x (7 + 5) - 4 x (7 + 4) = 12 x 12 - 4 x 11 = 144 - 44 = 100


La deuxième est impossible c'était pas plutôt 36 : 4 x 3
oui je me suis tromper 36:4+8=3
Donc 36 : (4 + 8) = 36 : 12 = 3
merci bcp
Derien :)